Individual Behavior as a Pathway between Early-Life Shocks and Adult Health: Evidence from Hunger Episodes in Post-War Germany - Iris Kesternich; Bettina Siflinger; James P. Smith; Joachim K. Winter (Institute for the Study of Labor (IZA), 2013)
We investigate long-run effects of episodes of hunger experienced as a child on health status and behavioral outcomes in later life. We combine self-reported data on hunger experiences from SHARELIFE, a retrospective survey conducted as part of SHARE in Europe in 2009, with administrative data on food supply (caloric rations) in post-war Germany. The data suggest that individual behavior is a pathway between early life shocks and adult health: We find that those who experienced hunger spend a larger fraction of income on food. Taken together, our results confirm that in addition to the well-documented biological channel from early life circumstances to adult health, there is also a behavioral pathway.
Keywords: I10; 330; war; health; income